Determination of Values of the Tricuspid Annular Plane Systolic Excursion (TAPSE) In Bangladeshi Adult Patient With or Without LV Dysfunction (Bangladesh Heart Journal, 2023)
Background: Tricuspid annular plane systolic excursion (TAPSE) is an Echocardiographic measure that allows us to assess right ventricular systolic function and  it correlates well with reference techniques like Cardiac Magnetic Resonance  Imaging. TAPSE measurement is common in adults.Objective: Our objective was to determine values of TAPSE in Bangladeshi adults with or without LV systolic dysfunction and to determine the relationship of these values with age, sex, RVIDd, LVEF & EPSS.Method: This was an   prospective observational study in patients undergoing comprehensive transthoracic echocardiography for any indication. From April  2022  to  April  2023 we prospectively enrolled 100 adult  (from 30 to age 80 years) of both sexes who presented to the Cardiology Clinic of  LABAID Cardiac  Hospital. We performed a complete transthoracic echocardiography  study. We measured TAPSE in 2-dimensional M-mode echocardiograms from the apical  4- chamber view, positioning the cursor on the lateral tricuspid annulus near the free RV wall and aligning it as close as possible to the apex of the heart . The mean values were taken by at least 2 measurements for reducing interobserver and intraobserver   variability’s.  Patients with confirmed congenital & valvular heart disease were excluded.Results: Mean TAPSE values were 19.15±3.87cm irrespective of LVEF, with no significant differences between sexes,  18.45±3.801  in male , 19.94±3.853 in female (P=.056).   TAPSE value was 22.00±1.581 in person with normal LVEF & 16.77±2.455 in person with reduced LVEF ( P